Primary infection with Herpes Simplex 1 virus on previous atopic dermatitis (eczema herpeticum). - Costa Ferreira Torres, T.; Vasconcelos, M.; Selores, M.M. (European Journal of Pediatric Dermatology, 2009)
Here was reported a case of herpetic eruption on previous atopic dermatitis. The causal agent was Herpes Simplex virus, as confirmed by the demonstration with polymerase chain reaction of the virus DNA in the fluid of vesicle.